Pressure-resistant, crack-resistant and fire-resistant cable insulating material and preparation method thereof
Through the combination of specific raw materials and process processing, pressure-resistant crack-resistant and refractory cable insulation materials are prepared, which solves the problem of unstable performance of existing materials in different environments, and achieves the comprehensive performance improvement of high mechanical strength, heat resistance and flame retardancy.
Patent Information
- Application Number
- CN202510081457.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing cable insulation materials have unstable performance in high temperature, strong sunshine, low temperature and other environments, and are not well-bearing and corrosion-resistant, which can easily lead to damage to the insulation layer and safety hazards.
Using specific raw materials, cross-linked polypropylene with acrylonitrile-butadiene-styrene and modified polymethyl methacrylate polymer materials are mixed with pressure-resistant and crack-resistant fire-resistant cable insulation material, and a composite mesh skeleton and specific flame retardant are built into the material.
It achieves the improvement of the mechanical strength, heat resistance, creep resistance and flame retardant properties of the material while maintaining good insulation performance, enhances pressure resistance, crack resistance and fire resistance, and reduces cost and energy consumption.
Smart Images

Figure BDA0005248775640000141
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cable insulation materials, and in particular to a pressure-resistant, crack-resistant and fire-resistant cable insulation material and a preparation method thereof. Background Art
[0002] Cable insulation material is an important component of wires and cables. Its main function is to ensure that current does not leak to the external environment during transmission, while protecting the cable from damage by the external environment.
[0003] There are many types of existing cable insulation materials. For example, polyvinyl chloride insulation has good insulation and chemical resistance, but it is prone to accelerated aging under high temperature or strong sunlight, and becomes hard and brittle at low temperatures; rubber insulation has good oil resistance, good softness and elasticity, and can maintain good performance in low temperature environments, but has weak mechanical strength and poor aging resistance; silicone rubber cable insulation is resistant to high temperatures, has good weather resistance, and has excellent electrical properties, but has insufficient wear resistance and corrosion resistance, and poor tear resistance. If it is squeezed or scraped by external force, it is easy to cause damage to the insulation layer, thereby causing safety hazards such as short circuits.
[0004] Therefore, there is an urgent need to provide a better cable insulation material that is not only safe and durable, but also has multiple functions such as pressure resistance, crack resistance, and fire resistance to meet different usage scenarios. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a pressure-resistant, crack-resistant and fire-resistant cable insulation material and a preparation method thereof. The pressure-resistant, crack-resistant and fire-resistant cable insulation material is prepared by selecting specific raw materials and adopting a specific method. While maintaining good insulation performance, it has good pressure resistance, crack resistance and fire resistance.
[0006] In a first aspect, the present application provides a pressure-resistant, crack-resistant and fire-resistant cable insulation material, which is implemented by the following technical solutions:
[0007] A method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material comprises the following steps:
[0008] (1) uniformly mixing 60-80 parts of polypropylene, 1-3 parts of 3-methacryloxypropyltrimethoxysilane, 25-40 parts of acrylonitrile-butadiene-styrene resin, 10-20 parts of modified polymethyl methacrylate resin, 2-4 parts of flame retardant and 0.5-1 parts of cross-linking catalyst according to weight parts to form a composite material precursor, heating and plasticizing the composite material precursor at a temperature of 190° C. to 230° C. to make it reach a molten state, and obtaining a fully mixed molten composite material;
[0009] (2) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material evenly through strong shearing action;
[0010] (3) placing the composite mesh skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely solidify it, so as to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material.
[0011] According to a method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to an embodiment of the present application, there are at least the following beneficial effects:
[0012] The preparation method of the present application adopts silane coupling agent to cross-link polypropylene, transforms the linear structure of polypropylene molecular chain into a three-dimensional network structure, improves the mechanical properties, heat resistance, melt strength and creep resistance of cross-linked polypropylene; and mixes with acrylonitrile-butadiene-styrene and modified polymethyl methacrylate polymer materials to further improve the mechanical strength and aging resistance of the material.
[0013] The preparation method of the present application pours the molten material into the interior of the composite mesh layer skeleton and melts and bonds them, thereby enhancing the bonding effect, causing the fibers to intertwine and bond with each other to form a high-strength reinforced skeleton, and enhancing the strength and crack resistance of the pressure-resistant, crack-resistant and fire-resistant cable insulation material.
[0014] The present application adopts microporous foaming injection molding. After being poured into the mold cavity, due to the sudden pressure drop and thermodynamic instability, the foaming agent precipitates inside the composite material to form a large number of bubble nuclei. In the subsequent cooling and molding process, the bubble nuclei continue to grow and solidify to form a microporous structure. Microporous foaming injection molding can effectively reduce costs and energy consumption. The prepared pressure-resistant, crack-resistant and fire-resistant cable insulation material has a large number of pore structures inside. The pore structure improves the pressure resistance of the pressure-resistant, crack-resistant and fire-resistant cable insulation material, and also has the characteristics of high specific strength and crack resistance. At the same time, the process is simple and the molding quality is high, which is suitable for industrial production.
[0015] According to some embodiments of the present application, the preparation of the modified polymethyl methacrylate resin in step (1) comprises the following steps:
[0016] 40-50 parts of polymethyl methacrylate resin, 0.4-0.6 parts of dicumyl peroxide and 1-2 parts of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 50-70 r / min, and reacted at 160-170° C. for 2-3 hours to obtain modified polymethyl methacrylate resin.
[0017] By modifying the polymethyl methacrylate resin, trimethylolpropane triacrylate can be grafted into the molecular chain structure of polymethyl methacrylate. Multiple double bonds in the same trimethylolpropane triacrylate molecule participate in the reaction, so that polymethyl methacrylate forms a cross-linked network structure, which broadens the molecular weight distribution of polymethyl methacrylate, thereby reducing its melt flow rate, having better thermal stability and faster cleaning rate during the foaming process, and being easier to process and shape.
[0018] According to some embodiments of the present application, the preparation of the composite mesh layer skeleton in step (3) includes the following steps: combing and laying basalt fibers to form a basalt fiber mesh layer, combing and laying aramid fibers to form an aramid fiber mesh layer, and then respectively compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer, and using the front and back needle punching method to completely penetrate the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton.
[0019] The basalt fiber of the present application has excellent modulus and strength, as well as good corrosion resistance, high temperature resistance, wear resistance, and excellent comprehensive performance; basalt fiber can also be radiation-proof, shock-proof, and resist fungal and microbial attacks, thereby increasing the service life of cable insulation materials; aramid fiber has excellent properties such as ultra-high strength, high modulus, high temperature resistance, acid and alkali resistance, light weight, aging resistance, and long life cycle, and can enhance the toughness and mechanical strength of pressure-resistant and crack-resistant cable insulation materials.
[0020] Furthermore, the basalt fiber is prepared by the following pretreatment method: sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; the basalt fiber is immersed in the pretreatment solution, and the basalt fiber is fully immersed by ultrasonic treatment to obtain the pretreated basalt fiber.
[0021] Furthermore, the aramid fiber is prepared by the following pretreatment method: sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; the aramid fiber is immersed in the pretreatment solution, and the aramid fiber is fully immersed by ultrasonic treatment to obtain the pretreated aramid fiber.
[0022] In the present application, the roughness of the surface of basalt fiber and aramid fiber can be greatly improved by using sodium hydroxide treatment, so that the bonding between them and acrylonitrile-butadiene-styrene resin and modified polymethyl methacrylate resin matrix is tighter; 3-aminopropyltriethoxysilane can react with basalt fiber, aramid fiber and acrylonitrile-butadiene-styrene resin and modified polymethyl methacrylate resin matrix respectively, so that a covalent bond connection similar to a bridge can be formed between basalt fiber, aramid fiber and acrylonitrile-butadiene-styrene resin and modified polymethyl methacrylate resin matrix, thereby improving the internal bonding stability of pressure-resistant, crack-resistant and fire-resistant cable insulation materials; ultrasonic treatment can make the fiber fully impregnated, ensuring that 3-aminopropyltriethoxysilane is evenly distributed on the surface of basalt fiber and aramid fiber.
[0023] Furthermore, the mass ratio of the aramid fiber to the basalt fiber is (2-3):(1-2).
[0024] Furthermore, the diameter of the aramid fiber is 10 μm-1000 μm.
[0025] Furthermore, the length of the aramid fiber is 1 cm-4 cm.
[0026] Furthermore, the diameter of the basalt fiber is 10 μm-1000 μm.
[0027] Furthermore, the length of the basalt fiber is 1 cm-4 cm.
[0028] According to some embodiments of the present application, the flame retardant in step (1) is a mixture of a phosphate flame retardant and fumed silica. When the material burns, silica can form a silica covering, which has the functions of insulation and shielding, and can prevent heat transfer and escape of combustibles. The addition of fumed silica can also increase the residual carbon content of the material. As its dosage increases, the residual carbon content of the composite material gradually increases, and the carbon layer gradually becomes denser and complete, effectively suppressing the flame, making the flame smaller and shorter, and reducing the heat and harm caused by the flame, thereby improving the flame retardant performance. At the same time, silica itself can also be further filled into the gaps of the polymer material to improve the mechanical properties and corrosion resistance of the pressure-resistant, crack-resistant and fire-resistant insulating material.
[0029] Furthermore, the phosphate flame retardant is triethyl phosphate. Triethyl phosphate has extremely low viscosity and high phosphorus content, and has good flame retardant effect.
[0030] Furthermore, the average particle size of the fumed silica is 25-35 nm, for example, the average particle size of the fumed silica is 30 nm. Nano-scale fumed silica can capture free radicals released by the combustion reaction and form a dense and uniform barrier layer, thereby enhancing the flame retardant effect.
[0031] Furthermore, the weight ratio of the fumed silica to the phosphate flame retardant is 1:(1-3), for example, the weight ratio of the fumed silica to the phosphate flame retardant is 1:2.
[0032] According to some embodiments of the present application, the cross-linking catalyst in step (1) includes at least one of organic tin and organic bismuth.
[0033] Furthermore, the cross-linking catalyst in step (1) includes at least one of dibutyltin diacetate, stannous octoate, dibutyltin dilaurate, and bismuth laurate.
[0034] In a second aspect, the embodiments of the present application provide a pressure-resistant, crack-resistant, and fire-resistant cable insulation material made by the preparation method of the pressure-resistant, crack-resistant, and fire-resistant cable insulation material.
[0035] A pressure-resistant, crack-resistant and fire-resistant cable insulation material according to an embodiment of the present application has at least the following beneficial effects:
[0036] The pressure-resistant, crack-resistant and fire-resistant cable insulation material of the present application is made of a mixture of cross-linked polypropylene with a silane coupling agent and acrylonitrile-butadiene-styrene and modified polymethyl methacrylate polymer materials, and has good mechanical properties. After foaming, it has good pressure resistance. The addition of a specific flame retardant improves the fire resistance. A composite mesh layer skeleton is built into the material and fused with the polymer material, which not only improves the mechanical strength of the pressure-resistant, crack-resistant and fire-resistant cable insulation material, but also enhances the anti-cracking performance. DETAILED DESCRIPTION
[0037] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0038] Example 1
[0039] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0040] (1) Sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; basalt fibers having a diameter of 500 μm and a length of 3 cm are immersed in the pretreatment solution, and the basalt fibers are fully immersed by ultrasonic treatment to obtain pretreated basalt fibers; aramid fibers having a diameter of 600 μm and a length of 2 cm are immersed in the pretreatment solution, and the aramid fibers are fully immersed by ultrasonic treatment to obtain pretreated aramid fibers; wherein the mass ratio of the aramid fibers to the basalt fibers is 2.5:1.5;
[0041] (2) combing and laying the pretreated basalt fibers to form a basalt fiber mesh layer, combing and laying the pretreated aramid fibers to form an aramid fiber mesh layer, and then compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer respectively, and using a front and back needle punching method to completely pierce the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton;
[0042] (3) 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate were mixed uniformly in a high-speed mixer according to weight parts, added to a torque rheometer at a speed of 60 r / min, and reacted at 165° C. for 2.5 hours to obtain a modified polymethyl methacrylate resin;
[0043] (4) 70 parts of polypropylene, 2 parts of 3-methacryloxypropyltrimethoxysilane, 32 parts of acrylonitrile-butadiene-styrene resin, 15 parts of modified polymethyl methacrylate resin, 3 parts of flame retardant and 0.8 parts of dibutyltin diacetate were mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor was heated and plasticized at a temperature of 210° C. to reach a molten state, thereby obtaining a fully mixed molten composite material;
[0044] (5) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0045] (6) placing the composite mesh layer skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely cure it to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0046] The flame retardant is a mixture of fumed silica with an average particle size of 30 nm and triethyl phosphate in a weight ratio of 1:2.
[0047] Example 2
[0048] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0049] (1) Sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; basalt fibers having a diameter of 1000 μm and a length of 1 cm are immersed in the pretreatment solution, and the basalt fibers are fully immersed by ultrasonic treatment to obtain pretreated basalt fibers; aramid fibers having a diameter of 1000 μm and a length of 1 cm are immersed in the pretreatment solution, and the aramid fibers are fully immersed by ultrasonic treatment to obtain pretreated aramid fibers; wherein the mass ratio of the aramid fibers to the basalt fibers is 3:1;
[0050] (2) combing and laying the pretreated basalt fibers to form a basalt fiber mesh layer, combing and laying the pretreated aramid fibers to form an aramid fiber mesh layer, and then compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer respectively, and using a front and back needle punching method to completely pierce the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton;
[0051] (3) 50 parts of polymethyl methacrylate resin, 0.4 parts of dicumyl peroxide and 2 parts of trihydroxypropane triacrylate were mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer at a speed of 50 r / min, and reacted at 170° C. for 2 h to obtain a modified polymethyl methacrylate resin;
[0052] (4) 80 parts of polypropylene, 1 part of 3-methacryloxypropyltrimethoxysilane, 40 parts of acrylonitrile-butadiene-styrene resin, 10 parts of modified polymethyl methacrylate resin, 4 parts of flame retardant and 0.5 parts of stannous octoate were mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor was heated and plasticized at a temperature of 230° C. to reach a molten state to obtain a fully mixed molten composite material;
[0053] (5) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0054] (6) placing the composite mesh layer skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely cure it to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0055] The flame retardant is a mixture of fumed silica with an average particle size of 25 nm and triethyl phosphate in a weight ratio of 1:3.
[0056] Example 3
[0057] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0058] (1) Sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; basalt fibers having a diameter of 10 μm and a length of 4 cm are immersed in the pretreatment solution, and the basalt fibers are fully immersed by ultrasonic treatment to obtain pretreated basalt fibers; aramid fibers having a diameter of 10 μm and a length of 4 cm are immersed in the pretreatment solution, and the aramid fibers are fully immersed by ultrasonic treatment to obtain pretreated aramid fibers; wherein the mass ratio of the aramid fibers to the basalt fibers is 2:2;
[0059] (2) combing and laying the pretreated basalt fibers to form a basalt fiber mesh layer, combing and laying the pretreated aramid fibers to form an aramid fiber mesh layer, and then compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer respectively, and using a front and back needle punching method to completely pierce the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton;
[0060] (3) 40 parts of polymethyl methacrylate resin, 0.6 parts of dicumyl peroxide and 1 part of trihydroxypropane triacrylate were mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer at a speed of 70 r / min, and reacted at 160° C. for 3 hours to obtain a modified polymethyl methacrylate resin;
[0061] (4) 60 parts of polypropylene, 3 parts of 3-methacryloxypropyltrimethoxysilane, 25 parts of acrylonitrile-butadiene-styrene resin, 20 parts of modified polymethyl methacrylate resin, 2 parts of flame retardant and 1 part of dibutyltin dilaurate are mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor is heated and plasticized at a temperature of 190° C. to reach a molten state to obtain a fully mixed molten composite material;
[0062] (5) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0063] (6) placing the composite mesh layer skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely cure it to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0064] The flame retardant is prepared by mixing fumed silica with an average particle size of 35 nm and triethyl phosphate in a weight ratio of 1:1.
[0065] Example 4
[0066] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0067] (1) Sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; basalt fibers having a diameter of 400 μm and a length of 2 cm are immersed in the pretreatment solution, and the basalt fibers are fully immersed by ultrasonic treatment to obtain pretreated basalt fibers; aramid fibers having a diameter of 600 μm and a length of 3 cm are immersed in the pretreatment solution, and the aramid fibers are fully immersed by ultrasonic treatment to obtain pretreated aramid fibers; wherein the mass ratio of the aramid fibers to the basalt fibers is 3:2;
[0068] (2) combing and laying the pretreated basalt fibers to form a basalt fiber mesh layer, combing and laying the pretreated aramid fibers to form an aramid fiber mesh layer, and then compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer respectively, and using a front and back needle punching method to completely pierce the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton;
[0069] (3) 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 2 parts of trihydroxypropane triacrylate were mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer at a speed of 60 r / min, and reacted at 165° C. for 3 hours to obtain a modified polymethyl methacrylate resin;
[0070] (4) 70 parts of polypropylene, 2 parts of 3-methacryloxypropyltrimethoxysilane, 30 parts of acrylonitrile-butadiene-styrene resin, 15 parts of modified polymethyl methacrylate resin, 3 parts of flame retardant and 0.7 parts of bismuth laurate were mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor was heated and plasticized at a temperature of 220° C. to reach a molten state to obtain a fully mixed molten composite material;
[0071] (5) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0072] (6) placing the composite mesh layer skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely cure it to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0073] The flame retardant is a mixture of fumed silica with an average particle size of 30 nm and triethyl phosphate in a weight ratio of 1:2.
[0074] Comparative Example 1
[0075] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0076] (1) Sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; basalt fibers having a diameter of 500 μm and a length of 3 cm are immersed in the pretreatment solution, and the basalt fibers are fully immersed by ultrasonic treatment to obtain pretreated basalt fibers; aramid fibers having a diameter of 600 μm and a length of 2 cm are immersed in the pretreatment solution, and the aramid fibers are fully immersed by ultrasonic treatment to obtain pretreated aramid fibers; wherein the mass ratio of the aramid fibers to the basalt fibers is 2.5:1.5;
[0077] (2) combing and laying the pretreated basalt fibers to form a basalt fiber mesh layer, combing and laying the pretreated aramid fibers to form an aramid fiber mesh layer, and then compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer respectively, and using a front and back needle punching method to completely pierce the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton;
[0078] (3) 70 parts of polypropylene, 2 parts of 3-methacryloxypropyltrimethoxysilane, 32 parts of acrylonitrile-butadiene-styrene resin, 15 parts of polymethyl methacrylate resin, 3 parts of flame retardant and 0.8 parts of dibutyltin diacetate were mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor was heated and plasticized at a temperature of 210° C. to reach a molten state, thereby obtaining a fully mixed molten composite material;
[0079] (4) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0080] (5) placing the composite mesh layer skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely cure it to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0081] The flame retardant is a mixture of fumed silica with an average particle size of 30 nm and triethyl phosphate in a weight ratio of 1:2.
[0082] Comparative Example 2
[0083] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0084] (1) 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate were mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer at a speed of 60 r / min, and reacted at 165° C. for 2.5 hours to obtain a modified polymethyl methacrylate resin;
[0085] (2) 70 parts of polypropylene, 2 parts of 3-methacryloxypropyltrimethoxysilane, 32 parts of acrylonitrile-butadiene-styrene resin, 15 parts of modified polymethyl methacrylate resin, 3 parts of flame retardant and 0.8 parts of dibutyltin diacetate were mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor was heated and plasticized at a temperature of 210° C. to reach a molten state, thereby obtaining a fully mixed molten composite material;
[0086] (3) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0087] (4) pouring the molten composite material uniformly mixed with the foaming agent into a mold cavity, then performing foaming molding, placing the composite material in a twin-screw extruder tabletting machine for tableting, and performing electron irradiation treatment through an irradiation process to completely cure the composite material to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0088] The flame retardant is a mixture of fumed silica with an average particle size of 30 nm and triethyl phosphate in a weight ratio of 1:2.
[0089] Comparative Example 3
[0090] Preparation of pressure-resistant, crack-resistant and fire-resistant cable insulation materials:
[0091] (1) Sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; basalt fibers having a diameter of 500 μm and a length of 3 cm are immersed in the pretreatment solution, and the basalt fibers are fully immersed by ultrasonic treatment to obtain pretreated basalt fibers; aramid fibers having a diameter of 600 μm and a length of 2 cm are immersed in the pretreatment solution, and the aramid fibers are fully immersed by ultrasonic treatment to obtain pretreated aramid fibers; wherein the mass ratio of the aramid fibers to the basalt fibers is 2.5:1.5;
[0092] (2) combing and laying the pretreated basalt fibers to form a basalt fiber mesh layer, combing and laying the pretreated aramid fibers to form an aramid fiber mesh layer, and then compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer respectively, and using a front and back needle punching method to completely pierce the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh layer skeleton;
[0093] (3) 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate were mixed uniformly in a high-speed mixer according to weight parts, added to a torque rheometer at a speed of 60 r / min, and reacted at 165° C. for 2.5 hours to obtain a modified polymethyl methacrylate resin;
[0094] (4) 70 parts of polypropylene, 2 parts of 3-methacryloxypropyltrimethoxysilane, 32 parts of acrylonitrile-butadiene-styrene resin, 15 parts of modified polymethyl methacrylate resin, 3 parts of flame retardant and 0.8 parts of dibutyltin diacetate were mixed uniformly according to weight parts to form a precursor of a composite material, and the composite material precursor was heated and plasticized at a temperature of 210° C. to reach a molten state, thereby obtaining a fully mixed molten composite material;
[0095] (5) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material uniformly through strong shearing action;
[0096] (6) placing the composite mesh layer skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely cure it to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material;
[0097] Wherein, the flame retardant is triethyl phosphate.
[0098] Experimental example
[0099] The pressure-resistant, crack-resistant and fire-resistant cable insulation materials prepared in Examples 1-4 and Comparative Examples 1-3 were tested for tensile strength, compressive strength, flame retardancy and corrosion resistance, respectively, and the test methods were as follows:
[0100] The tensile strength is tested according to the standard of GB / T 1040-92.
[0101] The compressive strength was tested according to the standard of GB / T 8813-2008, and the compressive stress when the relative deformation was 10% was recorded.
[0102] The flame retardant grade is tested according to the standard of GB 8624-2012.
[0103] The corrosion resistance is tested according to the standard of GB / T 3857-2017. If the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample remain unchanged, the corrosion resistance is recorded as level 1 (corrosion resistant); if at least one of the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample changes slightly, the corrosion resistance is recorded as level 2 (still corrosion resistant); if at least one of the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample changes significantly, the corrosion resistance is recorded as level 3 (not corrosion resistant).
[0104] The test data is shown in Table 1 below:
[0105] Table 1
[0106]
[0107] It can be seen from Table 1 that the pressure-resistant, crack-resistant and fire-resistant cable insulation materials prepared in Examples 1-4 of the present application have excellent mechanical properties such as compressive strength and tensile strength, and also have good corrosion resistance and flame retardancy.
[0108] The polymethyl methacrylate resin in the preparation raw materials of Comparative Example 1 has not been modified, and the rest is the same as Example 1. The corrosion resistance of the pressure-resistant, crack-resistant and fire-resistant cable insulation material prepared in Comparative Example 1 is significantly poor, and the compressive strength and tensile strength also decrease. This shows that in the present application, by modifying the polymethyl methacrylate resin, trimethylolpropane triacrylate can be grafted into the molecular chain structure of polymethyl methacrylate, and multiple double bonds in the same trimethylolpropane triacrylate molecule participate in the reaction to form a cross-linked network structure of polymethyl methacrylate, so that the molecular weight distribution of polymethyl methacrylate becomes wider, thereby reducing its melt flow rate, having better thermal stability and faster cleaning rate during the foaming process, being easier to process and shape, and improving the comprehensive performance of the pressure-resistant, crack-resistant and fire-resistant cable insulation material.
[0109] In the preparation process of Comparative Example 2, there is no composite mesh layer skeleton, and the rest are the same as Example 1. The compressive strength and tensile strength of the pressure-resistant, crack-resistant and fire-resistant cable insulation material prepared in Comparative Example 2 are significantly reduced, indicating that the preparation method of the present application pours the molten material into the interior of the composite mesh layer skeleton and melt-bonds it, thereby enhancing the bonding effect, causing the fibers to be intertwined and bonded to form a high-strength reinforced skeleton, thereby enhancing the strength and crack resistance of the pressure-resistant, crack-resistant and fire-resistant cable insulation material.
[0110] No fumed silica was added to the raw materials for the preparation of Comparative Example 3, and the rest were the same as Example 1. The flame retardancy of the pressure-resistant, crack-resistant and fire-resistant cable insulation material prepared in Comparative Example 3 was significantly deteriorated, and the compressive strength and tensile strength also decreased. The corrosion resistance was also not as good as the pressure-resistant, crack-resistant and fire-resistant cable insulation material of Example 1, indicating that fumed silica can not only improve the flame retardancy, but also silica itself can further fill the gaps in the polymer material, thereby improving the mechanical properties and corrosion resistance of the pressure-resistant, crack-resistant and fire-resistant cable insulation material.
[0111] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material, characterized in that: The following steps are involved: (1) uniformly mixing 60-80 parts of polypropylene, 1-3 parts of 3-methacryloxypropyltrimethoxysilane, 25-40 parts of acrylonitrile-butadiene-styrene resin, 10-20 parts of modified polymethyl methacrylate resin, 2-4 parts of flame retardant and 0.5-1 parts of cross-linking catalyst according to weight parts to form a composite material precursor, heating and plasticizing the composite material precursor at a temperature of 190° C. to 230° C. to make it reach a molten state, and obtaining a fully mixed molten composite material; (2) injecting supercritical carbon dioxide into the molten composite material as a foaming agent, and mixing the foaming agent and the molten composite material evenly through strong shearing action; (3) placing the composite mesh skeleton into a mold cavity, pouring the molten composite material uniformly mixed with the foaming agent, and then foaming and molding it, placing it in a twin-screw extruder to press the tablets, and performing electron irradiation treatment through an irradiation process to completely solidify it, so as to obtain a pressure-resistant, crack-resistant and fire-resistant cable insulation material.
2. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 1, characterized in that: The preparation of the modified polymethyl methacrylate resin in step (1) comprises the following steps: 40-50 parts of polymethyl methacrylate resin, 0.4-0.6 parts of dicumyl peroxide and 1-2 parts of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 50-70 r / min, and reacted at 160-170° C. for 2-3 hours to obtain modified polymethyl methacrylate resin.
3. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 1, characterized in that: The preparation of the composite mesh skeleton in step (3) comprises the following steps: combing and laying basalt fibers to form a basalt fiber mesh layer, combing and laying aramid fibers to form an aramid fiber mesh layer, and then respectively compounding the upper and lower surfaces of the basalt fiber mesh layer with a layer of aramid fiber mesh layer, and using the front and back needle-punching method to completely insert the aramid fibers of the aramid fiber mesh layer into the interior of the basalt fiber mesh layer to obtain a composite mesh skeleton.
4. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 3, characterized in that: The mass ratio of the aramid fiber to the basalt fiber is (2-3):(1-2).
5. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 3, characterized in that: The basalt fiber is prepared by the following pretreatment method: sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; the basalt fiber is immersed in the pretreatment solution, and the basalt fiber is fully immersed by ultrasonic treatment to obtain the pretreated basalt fiber; The aramid fiber is prepared by the following pretreatment method: sodium hydroxide and 3-aminopropyltriethoxysilane are mixed to form a pretreatment solution; the aramid fiber is immersed in the pretreatment solution, and the aramid fiber is fully immersed by ultrasonic treatment to obtain the pretreated aramid fiber.
6. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 1, characterized in that: The flame retardant in step (1) is a mixture of a phosphate flame retardant and fumed silica.
7. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 6, characterized in that: The average particle size of the fumed silica is 25-35 nm.
8. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 6, characterized in that: The weight ratio of the fumed silica to the phosphate flame retardant is 1:(1-3).
9. The method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to claim 1, characterized in that: The cross-linking catalyst in step (1) includes at least one of organic tin and organic bismuth.
10. A pressure-resistant, crack-resistant and fire-resistant cable insulation material prepared by the method for preparing a pressure-resistant, crack-resistant and fire-resistant cable insulation material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electric cable comprising foaming polyolefin isolator and manufacturing method thereof
CN101341553A
Method for making carbon dioxide physically foamed RF coaxial cable insulation cable core
CN101640083A
Coated central strength member for fiber optic cables with reduced shrinkage
US20080013899A1